Board Gender Diversity and Firm Performance in the US - Kroon, Zoe (2022)
This article examines the effect between board gender diversity and firm performance in US commercial banks, measured by the percentage of women on a board and return on average assets respectively. Looking at previous literature, there are five main theories that emerge to explain these effects seen and also a more recent vein of literature examining the effect of gender quotas. This study finds a statistically significant positive relationship between board gender diversity and firm performance, while controlling for numerous other variables. The results account for unobserved heterogeneity as well as heteroskedasticity, so the findings are robust.